2020
DOI: 10.1186/s12974-020-01963-6
|View full text |Cite
|
Sign up to set email alerts
|

The overexpression of TDP-43 in astrocytes causes neurodegeneration via a PTP1B-mediated inflammatory response

Abstract: Background Cytoplasmic inclusions of transactive response DNA binding protein of 43 kDa (TDP-43) in neurons and astrocytes are a feature of some neurodegenerative diseases, such as frontotemporal lobar degeneration with TDP-43 (FTLD-TDP) and amyotrophic lateral sclerosis (ALS). However, the role of TDP-43 in astrocyte pathology remains largely unknown. Methods To investigate whether TDP-43 overexpression in primary astrocytes could i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 85 publications
(100 reference statements)
2
49
0
Order By: Relevance
“…This indicates that the level of TDP-43 must be tightly regulated throughout life. GOF experiments also revealed that excess of TBPH or TDP-43 is highly toxic in muscles [ 270 , 306 , 307 ], glial cells [ 270 , 307 , 309 , 325 , 326 ], and in the eye [ 266 , 274 , 289 , 290 , 292 , 293 , 302 , 303 , 304 , 306 , 307 , 310 , 312 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 324 , 327 , 328 , 329 , 330 , 331 , 332 , 333 , 334 ]. Moreover, it was reported that TBPH or TDP-43 overexpression induces cell death, as was shown in motoneurons [ 266 , 289 , 290 , 301 ], glial cells [ 309 , 326 ], mushroom bodies [ 265 , 290 ], and in the eye.…”
Section: Tdp-43 Proteinopathy In the Fruit Flymentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates that the level of TDP-43 must be tightly regulated throughout life. GOF experiments also revealed that excess of TBPH or TDP-43 is highly toxic in muscles [ 270 , 306 , 307 ], glial cells [ 270 , 307 , 309 , 325 , 326 ], and in the eye [ 266 , 274 , 289 , 290 , 292 , 293 , 302 , 303 , 304 , 306 , 307 , 310 , 312 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 324 , 327 , 328 , 329 , 330 , 331 , 332 , 333 , 334 ]. Moreover, it was reported that TBPH or TDP-43 overexpression induces cell death, as was shown in motoneurons [ 266 , 289 , 290 , 301 ], glial cells [ 309 , 326 ], mushroom bodies [ 265 , 290 ], and in the eye.…”
Section: Tdp-43 Proteinopathy In the Fruit Flymentioning
confidence: 99%
“…This may explain some discrepancies between different GOF studies ( Table 9 and Table 10 ). Several phenotypes induced by TBPH /TDP-43 GOF, such as eye degeneration and climbing defects, show age-dependent progression [ 265 , 275 , 289 , 290 , 293 , 305 , 307 , 308 , 309 , 311 , 312 , 314 , 315 , 316 , 318 , 320 , 321 , 324 , 325 , 330 , 331 , 332 , 333 , 334 ]. As TBPH expression decreased with aging [ 338 ], one may speculate that reduced endogenous TBPH levels exacerbate GOF effects without excluding that phenotype aggravation may be due to continuous abnormal accumulation of TBPH /TDP-43.…”
Section: Tdp-43 Proteinopathy In the Fruit Flymentioning
confidence: 99%
See 2 more Smart Citations
“…To develop therapeutic interventions for neuroinflammatory and degenerative diseases, it is necessary to identify downstream signaling pathways of TDP-43 in reactive astrocytes. Lee et al recently revealed that TDP-43 overexpression in astrocytes causes neurodegeneration through a protein tyrosine phosphatase 1B (PTP1B)-mediated inflammatory response characterized by increased levels of inflammatory molecules, such as interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), lipocalin-2 (LCN2), and inducible nitric oxide synthase (iNOS) [ 22 ]. They also found that PTP1B regulates the inflammatory response via activation of the nuclear factor-κB (NF-κB) pathway, accompanied by increased phosphorylation of NF-κB subunit p65 in astrocytes.…”
Section: Introductionmentioning
confidence: 99%